Families’ experiences with a relative in the intensive care unit - Malliarou, Maria; Karathanasi, Konstantinia; Moustaka, Helen; Serafeim, Tatiana; Sotiriadou, Kiriaki; Sarafis, Pavlos (My University, 2011)
To (a) determine needs of families during the hospitalization of a family member in an ICU; (b) determine levels of satisfaction with how their needs were met.
Keywords: Family members; Satisfaction; Intensive care unit